[PP.35.06] HYPOVOLEMIC RENIN-ALDOSTERONE AXIS DEFICIENCY WITHOUT HYPERKALEMIA FOLLOWING UNILATERAL ADRENALECTOMY FOR PRIMARY ALDOSTERONISM. (September 2016) - Vallet, M.; Martin, A.; Huyghe, E.; Amar, J.; Chamontin, B.; Tack, I.; Bouhanick, B.
Abstract : Objective: A ldosterone-producing adenoma is classically treated by unilateral adrenalectomy. Severe hyperkalemia, related to hypoaldosteronism, have been already reported after surgery. We hereby describe six male patients exhibiting prolonged failure of the renin-aldosterone (RA) axis, in association with normal-to-high kalemia or labile blood pressure and, most significantly, decrease in extracellular fluid volume (ECFV). Design and method: Primary aldosteronism diagnosis was established according to French recommendations. Unilateral adrenalectomy was performed in all. Postoperative explorations included ECFV measurement using inulin, and RA axis functionally tests by orthostatic and ACTH stimulation. Results: A decrease in ECFV with inappropriately low renin level, and insufficient orthostatism-induced aldosterone production were depicted. The ACTH test demonstrated no glucocorticoid deficiency, along with responsive aldosterone secretion. The discrepancy in aldosterone response in orthostatic position versus ACTH stimulation test suggested that hypoaldosteronism primarily results from the lack of angiotensin 2 stimulation as a result of hyporeninism. Figure. No caption available. Conclusions: Following unilateral adrenalectomy for primary aldosteronism, the occurrence of normal-to-high kalemia prompted an evaluation of the RA system using orthostatic stimulation test rather than simply measuring baseline values and evaluating the glucocorticoid axis. When confirmed, RA axis depression causes latent hypovolemia, meaning that all treatment likely to further decrease plasma volume should be avoided, while this may at times require mineralocorticoid substitution.